A Sustained-Release Membrane of Thiazolidinedione-8: Effect on Formation of a Candida/Bacteria Mixed Biofilm on Hydroxyapatite in a Continuous Flow Model. (10th October 2017) - Feldman, Mark; Shenderovich, Julia; Lavy, Eran; Friedman, Michael; Steinberg, Doron
Abstract : Thiazolidinediones (TZDs) have been found to act as effective quorum sensing quenchers, capable of preventing biofilm formation. Our previous studies demonstrated a profound antibiofilm effect of the TZD derivative thiazolidinedione-8 (S-8), either in solution or incorporated into a sustained-release membrane (SRM-S-8) under batch conditions. In the present study, we used a constant depth film fermenter model in order to investigate the impact of SRM-S-8 on mixed C. albicans - S. mutans biofilm development, under flow conditions. We found that essential parameters of cospecies biofilm maintenance and maturation, such as metabolic activity, biofilm thickness, roughness, extracellular polysaccharides production, and morphology of both pathogens, were altered by SRM-S-8 in the flow system. We propose that prolonged and sustained release of S-8 in a flow-through system allows better penetration of the active agent to deeper layers of the mixed biofilm, thereby increasing its activity against both pathogens. In conclusion, the use of a locally applied sustained-release drug delivery system of S-8 can affect the dental polymicrobial biofilm, resulting in clinical improvements and a better patient compliance.